David J. Brewer : the life of a Supreme Court justice, 1837-1910 - Brodhead, Michael J. (Southern Illinois University Press, 1994)
This informative new book is the first biography of David J. Brewer, an Associate Justice of the United States Supreme Court from 1889 to 1910 and certainly one of the most visible judges of his time. Michael J. Brodhead's candid account covers Brewer's entire judicial career as well as his childhood, education, personal life, and many and varied public activities. Prior to rising to the nation's highest tribunal, Brewer served as a county probate judge, a state district judge, a Kansas State Supreme Court justice, and a federal circuit court judge. He was known not only for his long tenure on the Supreme Court but also for his numerous off-the-bench statements as an orator and writer.
Keywords: Brewer, David J. -- (David Josiah), -- 1837-1910.; United States. -- Supreme Court -- Biography.; États-Unis. -- Supreme Court -- Biographies.; Brewer, David J. -- (David Josiah), -- 1837-1910; United States. -- Supreme Court; Judges -- United States -- Biography.; Juges -- États-Unis -- Biographies.; LAW -- Government -- Federal.; POLITICAL SCIENCE -- Government -- Judicial Branch.; LAW -- Legal Services.; LAW -- Civil Procedure.; BIOGRAPHY & AUTOBIOGRAPHY -- Lawyers & Judges.; Judges; United States; Law - U.S.; Law, Politics & Government.; Law - U.S. - General.; dissertations.; Biographies; Academic theses.; Thèses et écrits académiques.